Self-Planning Traveller System / Khor Chun Siang … [et al.] - Khor, Chun Siang; Abdullah, Nasuha Lee; Idrus, Rosnah (Research Management Institute (RMI), 2017)
This study aimed to understand the problems faced by self-planning travellers when they plan for a trip by searching travel information from the Internet and propose a system to facilitate the self-planning travellers to obtain useful travel information. An online survey was conducted via social media to understand the problems, the search criteria and types of content of travel itinerary needed in facilitating the planning. A total of 65 responses were collected. The results showed that there were too many unrelated information on the Web and travellers were unsure of where to start the search. Also, the result revealed that the search criteria needed to generate travel itinerary were travel date, travel duration, travel country and travel budget. Finally, flight schedule, hotel accommodation, sightseeing places, travelling route and things to do were the information required by travellers for their travel itineraries. Based on the results, a travel itinerary recommendation system named eTravelPlanner is proposed.